Effectiveness of group‐based self‐management education for individuals with Type 2 diabetes: a systematic review with meta‐analyses and meta‐regression. Issue 8 (20th March 2017) - Odgers‐Jewell, K.; Ball, L. E.; Kelly, J. T.; Isenring, E. A.; Reidlinger, D. P.; Thomas, R.
Abstract: Aims: Patient education for the management of Type 2 diabetes can be delivered in various forms, with the goal of promoting and supporting positive self‐management behaviours. This systematic review aimed to determine the effectiveness of group‐based interventions compared with individual interventions or usual care for improving clinical, lifestyle and psychosocial outcomes in people with Type 2 diabetes. Methods: Six electronic databases were searched. Group‐based education programmes for adults with Type 2 diabetes that measured glycated haemoglobin (HbA1c ) and followed participants for ≥ 6 months were included. The primary outcome was HbA1c, and secondary outcomes included fasting blood glucose, weight, body mass index, waist circumference, blood pressure, blood lipid profiles, diabetes knowledge and self‐efficacy. Results: Fifty‐three publications describing 47 studies were included ( n = 8533 participants). Greater reductions in HbA1c occurred in group‐based education compared with controls at 6–10 months [ n = 30 studies; mean difference (MD) = 3 mmol/mol (0.3%); 95% confidence interval (CI): −0.48, −0.15; P = 0.0002], 12–14 months [ n = 27 studies; MD = 4 mmol/mol (0.3%); 95% CI: −0.49, −0.17; P < 0.0001], 18 months [ n = 3 studies; MD = 8 mmol/mol (0.7%); 95% CI: −1.26, −0.18; P = 0.009] and 36–48 months [ n = 5 studies; MD = 10 mmol/mol (0.9%); 95% CI: −1.52, −0.34; P = 0.002], but not at 24 months. Outcomes also favoured group‐based education for fasting blood glucose, body weight, waist circumference, triglyceride levels and diabetes knowledge, but not at all time points. Interventions facilitated by a single discipline, multidisciplinary teams or health professionals with peer supporters resulted in improved outcomes in HbA1c when compared with peer‐led interventions. Conclusions: Group‐based education interventions are more effective than usual care, waiting list control and individual education at improving clinical, lifestyle and psychosocial outcomes in people with Type 2 diabetes. What's new?: We present a comprehensive up‐to‐date review of the evidence for the effectiveness of Type 2 diabetes group‐based interventions. This is the first review in the area to complete a meta‐regression. We report statistically significant results for improving HbA1c, fasting blood glucose, body weight, waist circumference, triglycerides and diabetes knowledge, but clinical improvement is more nuanced. Group‐based interventions facilitated by a single discipline, multidisciplinary teams or health professionals with peer supporters appear to be more effective at improving HbA1c than peer‐led interventions.